Advanced Peptide Nanomedicines for Bladder Cancer Theranostics - Zeng, Sheng; Feng, Xiaodi; Xing, Shaoqiang; Xu, Zhaoliang; Miao, Zhizhao; Liu, Qian (Frontiers in Chemistry, 2022)
Cancer is still a global public health problem. Although remarkable success has been achieved in cancer diagnosis and treatment, the high recurrence and mortality rates remain severely threatening to human lives and health. In recent years, self-assembling peptide nanomedicines with precise selectivity and high biocompatibility have attracted intense attention in biomedical applications. In particular, there has been a significant increase in the exploration of peptides and their derivatives for malignant tumor therapy and diagnosis. Herein, we review the applications of peptides and their derivatives in the diagnosis and treatment of bladder cancer, providing new insights for the design and development of novel peptide nanomedicines for the treatment of bladder cancer in the future.